"Download for Free": When do providers of digital goods offer free samples? - Anette Boom (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
In a monopoly setting where consumers cannot observe the quality of the product we show that free samples which are of a lower quality than the marketed digital goods are used together with high prices as signals for a superior quality if the number of informed consumers is small and if the difference between the high and the low quality is not too small. Social welfare is higher, if the monopolist uses also free samples as signals, compared to a situation where he is restricted to pure price signalling. Both, the monopolist and consumers benefit from the additional signal.
Keywords: 330